Update of Hulse´s Technique for the Surgical Correction of Cranial Cruciate Ligament Rupture and Its Long-Term Postoperative Evaluation in a Group of Canines - de Aurrecoechea, Claudia; Pinhas, Álvaro (Universitas Airlangga, 2025)
Rupture of the cranial cruciate ligament is the oldest and most prevalent cause of osteoarthrosis (OA) of the patellofemoral joint (PFJ) in canines, being 75% of all PFJ surgical pathologies. To assess the long term clinical, radiological and orthopaedic results of a modification of Hulse’s technique for intracapsular surgical correction of cranial cruciate ligament rupture (CrCLR). A heterogeneous population of 12 canines who had undergone surgery for CrCLR was called for the study, of which 3 underwent surgery on both PFJs. The technique was modified by using a pre folded crochet needle and a tiny lateral arthrotomy performed just under the lateral collateral ligament. This study was done after 20 months on average from de surgery (range 8 to 36 months) and all the surgeries were performed by the same surgeon. All animals were monitored during the study period, which lasted 4 months. A blind radiological assessment of 3 observers was performed using the Bioarth scale, an orthopaedic assessment to quantify the degree of claudication and PFJ angles (goniometry) and two scales were also used for the assessment of chronic pain and animal welfare i.e., Helsinki's scale and CPBI (canine pain brief inventory). The radiographic assessment of OA yielded a mean of 9.13, with SD of 5.50 and a SE of 1.42. The average subjective assessment of OA according to the Bioarth scale was moderate. The qualitative orthopedic assessment showed that 7 patients did not present claudication, 4 patients showed grade 1 claudication and one grade 2. The CPBI and Helsinki animal welfare scales showed an excellent subjective assessment by the tutors. The Hulse technique, modified with a crochet needle, was sufficient to surgically correct the CrCLR in an heterogeneous population of 12 canines, achieving that all patients functionally used the operated limb or limbs, possessing a very good to excellent quality of life according to their owners, despite having evidenced a moderate degree of OA with an average of 9.13 on the Bioarth scale.